Smart Solar Wheelchair Controlled Using Android App And Joystick - et. al., Sowmya CH, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The proposed project is designed to provide support for physically handicapped persons and patients who use wheelchairs, to navigate in an aerial map without any external support. Traditionally, the wheel chairs were equipped with pedals where the patient had to navigate using peddling. There was a wheel chair model where the patient used their hands to move the wheel mechanically.In our proposed model, the locomotion of the wheel chair is achieved electrically. The logic of the electric wheelchair can be controlled by a wired panel as well as through an android app with wifi module ESP8266 . The system also has the feature to alert the caretaker and their families during emergencies. The patient has to press the emergency button to intimate the emergency to their family.The system also has an auto collision detection system, using ultrasonic signals. It saves the patient from collision, due to system fault. The battery is charged through solar panels. The solar panels are connected to the battery, which gets charged due to solar power.